Optimal Control Strategy on the Transmission Dynamics of Herpes Simplex Virus-II (HSV-II) - Gurmu, Eshetu Dadi; Bole, Boka Kumsa; Koya, Purnachandra Rao (Applications of Modelling and Simulation, 2021)
In this paper, optimal control theory is applied to Herpes Simplex Virus-II transmission model given by a system of non-linear ordinary differential equations. Optimal control strategy was employed to study the level of effort needed to control the transmission dynamics of HSV-II diseases using three controls; prevention, screening and treatment control strategies. The necessary conditions for the existence of the optimal controls was established using Pontryagin’s Maximum Principle. Optimal control system was performed with help of Runge-Kutta forward-backward sweep numerical approximation method. Finally, numerical simulations reveal that a combination of prevention, screening and treatment is the most effective strategy to eradicate the disease from the community.